(untitled) (Revista Rupturas, 2025)
The research on the gender of authorship in opinion articles from Semanario Universidad (2023-2024) highlights the need to apply “gender mathematics” in public spaces as a tool to evaluate the representation of women and non-binary people. Despite legal advances, 79.92% of the publications correspond to commonly masculine names, compared to 17.08% with commonly feminine names. The challenge of binary gender data based on names is acknowledged, as it limits the recognition of diverse identities. The study concludes that Semanario reflects historical structural inequalities, underscoring the importance of implementing affirmative measures, collecting inclusive data, and formulating public policies to promote gender equality and parity in the media, in line with international commitments.